Solution chemistry-based nano-structuring of copper dendrites for efficient use in catalysis and superhydrophobic surfaces - Bakthavatsalam, Rangarajan; Ghosh, Subrata; Biswas, Ratul Kumar; Saxena, Aayushi; Raja, Alagar; Thotiyl, Musthafa Ottakam; Wadhai, Sandip; Banpurkar, Arun G.; Kundu, Janardan (RSC Advances, 2016)
Despite their performance and economic advantages over Ag and Au, there have been no focused research efforts on the nano-structuring of Cu dendrites with respect to fine-tuning their structure/morphology towards the efficiency enhancement of suitable applications. Reported here is a simple, versatile, environmentally-friendly and galvanic replacement reaction-based solution chemistry methodology to synthesize highly nano-structured copper dendrites targeted towards the efficiency enhancement of desired applications. Herein, copper is deposited galvanically on an Al foil in the presence of NaCl/HCl, wherein the chloride anions augment an uninterrupted replacement reaction. The growth process of Cu dendrites has been probed in detail. The presence of acid, the type of Cu2+ precursor salt, the Cu2+ ion concentration, the surfactant concentration and the reaction temperature are all demonstrated to provide useful means of modulating the surface structure/morphology of the dendrites. Notably, dendrites formed in the presence of acid are found to be highly nano-structured. Moreover, it is also found that the morphology/structure of the obtained Cu deposit depends considerably upon the choice of the Cu2+ precursor salt, a parameter that has been completely overlooked in the past. The acid-induced nano-structuring of the dendrites is exploited for enhancing their efficiency in the catalytic reduction of para-nitrophenol and for fabricating self-cleaning superhydrophobic surfaces. These nano-structured dendrites are demonstrated to have the highest ever normalized rate constant for the catalytic reduction reaction. Superhydrophobic surfaces fabricated using these dendrites demonstrate excellent self-cleaning abilities, showing a high contact angle (159 degrees) with low contact angle hysteresis (2 degrees). This facile synthetic strategy for the fabrication of highly nano-structured Cu dendrites is expected to open up avenues for the production of Cu-based low-cost functional nano/micro-materials.

Synthetic control on structure/dimensionality and photophysical properties of low dimensional organic lead bromide perovskite - Haris, Muhammed P. U.; Bakthavatsalam, Rangarajan; Shaikh, Samir; Kore, Bhushan P.; Moghe, Dhanashree; Gonnade, Rajesh G.; Sarma, D. D.; Kabra, Dinesh; Kundu, Janardan (Inorganic chemistry, 2018)
Low dimensional lead halide perovskites have attracted huge research interest due to their structural diversity and remarkable photophysical properties. The ability to controllably change dimensionality/structure of perovskites remains highly challenging. Here, we report synthetic control on structure/dimensionality of ethylenediammonium (ED) lead bromide perovskite from a two dimensionally networked (2DN) sheet to a one dimensionally networked (1DN) chain structure. Intercalation of solvent molecules into the perovskite plays a crucial role in directing the final dimensionality/structure. This change in dimensionality reflects strongly in the observed differences in photophysical properties. Upon UV excitation, the 1DN structure emits white light due to easily formed “self-trapped” excitons. 2DN perovskites show band edge blue emission (∼410 nm). Interestingly, Mn2+ incorporated 2DN perovskites show a highly red-shifted Mn2+ emission peak at ∼670 nm. Such a long wavelength Mn2+ emission peak is unprecedented in the perovskite family. This report highlights the synthetic ability to control the dimensionality/structure of perovskite and consequently its photophysical properties.

Synergistic electronic coupling/cross-talk between the isolated metal halide units of zero dimensional heterometallic (Sb, Mn) halide hybrid with enhanced emission - Biswas, Anupam; Bakthavatsalam, Rangarajan; Das, Deep K.; Sam, Jisvin; Mali, Bhupendra P.; Biswas, Chinmoy; Maana, Narugopal; Thomson, Stuart; Raavi, Sai Santosh Kumar; Kurungot, Sreekumar; Gonnade, Rajesh G.; Dutta, Sudipta; et al. (Journal of Materials Chemistry C, 2021)
Heterometallic 0D metal halide hybrids, consisting of more than one kind of metal halide units, are anticipated to manifest synergistic effects on the photo-physical properties of the constituent metal halide units. Such architectures hold great promise for design and development of function-targeted materials. However, heterometallic 0D hybrids, featuring isolated metal halide units, typically do not show any synergistic effects due to large inter-unit spatial separations that inhibit interactions/coupling between the constituent metal halide units. It remains challenging to design synthetic strategies that would support structural modifications to allow synergistic electronic coupling between the metal halide units in heterometallic 0D hybrids. Here, we report synthesis and characterization of heterometallic (Sb, Mn) 0D hybrid, namely Tris SbMnCl, with isolated MnCl5 units, (Sb/Mn)Cl-6 units, dispersed in the organic ligand matrix and layer of dynamic and networked water molecules. Steady state and time resolved emission spectra (TRES) analysis suggests strong synergistic interaction between the isolated metal halide units. Efficient energy transfer from the strongly absorbing Sb centres to emissive Mn centres results in the observed enhanced emission. Proton conductivity measurements together with first-principles calculations suggest the unique role of the networked water molecules in mediating the electronic coupling/energy transfer between the separated metal halide units in Tris SbMnCl hybrid. This report highlights the role of structure/composition of the synthesized heterometallic 0D hybrid in attaining electronic dimensionality higher than 0D through synergistic electronic interaction between the isolated metal halide units.